Casablanca [videorecording (Blu-Ray)] - Alison, Joan (Turner Entertainment : Distributed by Warner Home Video, 2012)
The romantic lovers' triangle between the impossibly heroic Czech Resistance leader Victor Laszlo, his beautiful wife Ilsa and her ex-lover, cynical American Rick Blaine is still the same old story, but it's never looked better.